High‐Performance MXene Hydrogel for Self‐Propelled Marangoni Swimmers and Water‐Enabled Electricity Generator - Jiayi Zhou; Yan Zhang; Ming Zhang; Dongye Yang; Wenwei Huang; Ao Zheng; Lingyan Cao (Advanced Science)
Abstract Developing multifunctional materials that integrate self‐propulsion and self‐power generation is a significant challenge. This study introduces a high‐performance MXene‐chitosan composite hydrogel (CM) that successfully combines these functionalities. Utilizing Schiff base bond and hydrogen bond interactions, the CM hydrogel, composed of chitosan, vanillin, and MXene, achieves exceptional self‐propulsion on water driven by Marangoni forces. The hydrogel demonstrates rapid movement, extended operation, and controllable trajectories. Notably, the CM hydrogel also exhibits superior degradability, recyclability, and repeatability. Furthermore, the nano‐confined channels within the hydrogel play a crucial role in enhancing its water‐enabled electricity generation (WEG) performance. By efficiently adsorbing water molecules and selectively transporting cations through these channels, the hydrogel can generate electricity from water molecules and cations more efficiently. As a result, the CM‐WEG achieves a stable open‐circuit voltage of up to 0.83 V and a short‐circuit current of 0.107 mA on seawater, with further improvements in K2CO3‐containing water, reaching 1.26 V and 0.922 mA. Leveraging its unique combination of self‐propulsion and WEG functionalities, the CM hydrogel is successfully used for cargo delivery while simultaneously powering electronic devices. This research represents a significant step toward the development of self‐powered, autonomous soft robotics, opening new research directions in the field.